Fortalecimiento del proyecto de ética y valores para la prevención del suicidio en los adolescentes de la Institución educativa Ecológico el Carmen Sede 1 del Distrito Especial, Turístico y Cultural de Riohacha (2020)
The purpose of this research is to strengthen the project of ethics and values of the Ecological Educational Institution El Carmen of Riohacha District, for the prevention of suicide in adolescents through a theoretical humanistic approach using a qualitative methodology and a type of phenomenological design, which allowed analyzing the information from the perceptions of the participants through the application of in-depth interviews. In this sense, among the main findings are the family context as the area with the highest prevalence as a risk factor, the result of psychological disorders in students. In relation, the need for the permanent and effective presence of psych-orientation support is evident. From the foregoing, it is concluded that in response to the needs expressed by the interviewees, the strengthening of psycho-pedagogical strategies that contribute to the support of the role of the teacher is required in order to reduce the difficulties of the academic process of the students and above all to prevent the absence of the meaning of life.